Anti-tuberculosis and cytotoxic evaluation of the seaweed Sargassum boveanum - Vajihe Akbari; Saeed Zafari; Afsaneh Yegdaneh (Wolters Kluwer Medknow Publications, 2018)
Marine seaweeds produce a variety of compounds with different biological activities, including antituberculosis and anticancer effects. The aim of this study was to investigate anti-tuberculosis activity of Sargassum boveanum (S. boveanum) and cytotoxicity of different fractions of this seaweed. S. boveanum was collected from Persian Gulf. The plant was extracted by maceration with methanol-ethyl acetate solvent. The extract was evaporated and partitioned by Kupchan method to yield hexane, tricholoroethane, chloroform, and butanol partitions. The anti-tuberculosis activity of the crude extract and toxicity of the fractions were investigated using green fluorescent protein reporter microplate assay and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay methods, respectively. The cell survivals of HeLa cell were decreased by increasing the concentration of the extracts. The IC50 values of hexane, tricholoroethane, chloroform, and butanol partitions were 150.3 ± 23.10, 437.0 ± 147.3, 110.4 ± 33.67, and 1025.0 ± 15.20 μg/mL, respectively. The crude extract was not active against tuberculosis. This study reveals that different partitions of S. boveanum have cytotoxic activity against the cancer cell lines.